Evaluation of the Multiple Regression Analysis Algorithm on Stock Market Prediction - Setiawan, Mohamat; Maturidi, Ade Johar; Novianti, Dian (Ann Publisher, 2024)
Financial time series is one of the most challenging applications of modern time series forecasting. The financial time series is closely related to noise, non-stationary, and deterministic chaos. The characteristics suggest that no complete information can be obtained from the past behavior of financial markets to fully capture the dependency between future prices and that of the past. The data collection method was collected from the Stock Market Online Application